A study to evaluate the effectiveness of competency-based training program for the dental interns of a tertiary care center in Jaipur city - Kopal Sharma; Amit Sharma; Kanu Neemawat (Wolters Kluwer Medknow Publications, 2020)
Background: The purpose of our study was to ascertain the effectiveness of competency-based training model for dental interns. Materials and Methods: This competency-based integrated training program was conducted for the dental interns of a dental college in Jaipur city. Clinical vignettes, interactive video lectures, webinar sessions, group discussions, and multiple-choice questions were the components of our training module. The whole program was divided into five modules, which were planned meticulously to achieve five different learning objectives. Before starting each module and at its completion, the students were evaluated for their performance by the same multiple-choice questions and the feedback of the students was taken. Results: The respondents included 8 (16.67%) males and 40 (83.33%) females, with a mean age of 22.34 ± 0.78 years. An increase in overall mean score was found in the posttest for all the five modules, and this was statistically significant with P < 0.001 using the Wilcoxon signed-rank test. Conclusion: Competency-based training program for the dental interns was very effective in training them various skills and knowledge that cannot be merely achieved by traditional teaching methodology. More integrated programs are warranted for dental undergraduates to train them to become a skilled practitioner.